Consumer perception of a decorative cosmetic brand in the CZ/SK market : A case study of L’Oréal Maybelline New York. - Široká, Natálie (2025)
This thesis investigates the perception of Maybelline New York among Gen Z and Millennial consumers in the CZ/SK/HU markets and its influence on their purchasing behaviour. To achieve this, the research combines a literature review and desk research with primary data from semi-structured interviews and a quantitative survey. The collected data were then analysed through thematic, descriptive, and statistical methods. Findings reveal Maybelline New York’s successful positioning as a higher-quality mass-market brand, where perceived quality justifies a mid-range price. However, this is coupled with a fragmented brand equity, overwhelmingly driven by viral “hero” products, as consumer trust does not automatically extend to the wider portfolio. Furthermore, a generational divide presents a consumer lifecycle challenge, as maturing consumers may perceive the brand as too young. The study concludes that MNY must implement a strategy that leverages its hero products to build portfolio-wide trust and evolves its communication to retain maturing consumers through an integrated digital-to-physical journey.